Coming Home to School: Challenges and Strategies for Effective Teaching with Military Veterans - Michel A. Sportsman; Lisa Thomas (InSight, 2015)
This article is an analysis of the unique needs of returning service members at the college or university level that impact the teaching decisions made by instructors. The article also discusses the challenges that service members are individually addressing while acclimating themselves to their new environment of learning. With the reduction in forces occurring after the Iraq and Afghanistan wars, many higher level learning institutions are struggling to adequately meet the needs of returning veterans. In turn, veterans often find that the style of instruction and the general college-level universe are difficult to negotiate. The combination of these factors can often result in veteran students performing below expectation of leaving school without finishing. The article proposes a variety of ways to understand and address these challenges including the use of Scholarship of Teaching and Learning (SoTL) strategies and characteristics.